If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(5t+6)-2(4+2t)=10
We simplify the equation to the form, which is simple to understand
(5t+6)-2(4+2t)=10
Remove unnecessary parentheses
5t+6-2*(4+2t)=10
Reorder the terms in parentheses
5t+6+(-8-4t)=10
Remove unnecessary parentheses
+5t+6-8-4t=+10
We move all terms containing t to the left and all other terms to the right.
+5t-4t=+10-6+8
We simplify left and right side of the equation.
+1t=+12
We divide both sides of the equation by 1 to get t.
t=12
| 3(2x-1)=3 | | P=2(65)+2(137) | | 9-(x+1)/(6)=(x+7)/(10) | | 6x-7y-28=0 | | 5x-74=0 | | 14-5x-8-x=3+15-12x-6x | | 6x-2x-3=5 | | -16(4m-5n+2p)= | | 3x/7+x/14 | | r+4=3r-6 | | 5r+6-3r+7= | | x-2100=8939 | | 5+6x=8x-12 | | 5/7-6/8 | | -2(n+6)=-12-2n | | -4-(3-2p)= | | -2(n+6)=-12-12n | | -6(11-2t)=7(-2-2t) | | 20-12= | | 3x+x=560 | | 6x^8-7x^3+7x^2+8+7x^7+4x^3-9x= | | 0.04(y-7)+0.18y=0.12y-0.4 | | 5x^2+(3/5)x+(12/25)=0 | | 14+x=37+2x | | 42-5(4+2)/3 | | 216.75=(x-6)(x-6)(3) | | 2x+50=12 | | x+306=3306 | | 3(x-2)+2x=4x+14 | | 25x^2+3x+12=0 | | 25x^2+3x+12= | | X+3y+2=0 |